Estrategias para mejorar el servicio al cliente en las instituciones públicas de la ciudad de Latacunga - Shulca Guamán, Blanca Yolanda (2015)
The investigation has been done to look for strategies and to improve the customer service in the Public Institutions of Latacunga city and to determine the weaknesses that exists about the customer service. The aim of this investigation is to improve the customer service of each one of the Public Institutions, through the use of the suitable strategies that will allow them to develop the efficient performance of the activities. These strategies are targeted to optimize the customer support and in this way to offer a quality service to each and every one of them….